Chitosan and oral mucosal wound healing in dentistry—Journey from non-patented to patent introspection from 2010–2021 - Meenakshi S, Raghunath N, Ramith Ramu (Journal of Applied Pharmaceutical Science, 2022)
Wounds are frequently formed when the anatomy and physiology in the normal state of the oral mucosa are disrupted. Its recovery is a multi-staged, complicated, and dynamic biological process. While several biopolymeric derivatives are available for wound healing. Chitosan (CS) is among the well-known, innovative, and eye-catching materials. CS is a polysaccharide biopolymer with a lot of potential for boosting wound healing. Most significantly, CS derivatives have piqued the scientific community’s interest as a therapeutic and include them in a variety of formulations to facilitate wound healing. The primary goal of this paper is to offer a scientific as well as technical perspective on CS and its derivatives for oral mucosal wound healing activities between 2010 and 2021. Furthermore, the study focuses on the use of various therapeutic alternatives using CS that is presently being evaluated in clinical trials for wound healing, as well as its integration into polymethyl methacrylate to improve its characteristics for use in dentistry.
Keywords: Chitosan, prospection, patent classification, patent analysis, biopolymer, mucosal wound healing